Respuestas

  • Usuario de Brainly
2013-05-09T14:49:59+02:00

21-6x=27-8x

21 - 27 = - 8x + 6x

- 6 = - 2x

-6/-2 = x

3 =x

 

 

 

 

11x+5x-1=65x-36

11x +5x - 65x = - 36 + 1

 - 49x = - 35

x = -35/-49

x = 35/49

x = 5/7

 

 

 

8x-4+3x=7+x+14

8x + 3x -x = 7 +14 + 4

10x = 25

x = 25/10

x = 2,5

 

 

 

 

8x+9-12=4x-13-5x

8x -4x + 5x = - 13 + 12 - 9 

9x = -1

x = - 1/9

 

 

 

5y+6y-81=7y+102+65y

5y + 6y - 7y - 65y = 102 +81

-61y = 183/-61

y = - 3

 

 

espero que te sirva, salu2!!!